THE IMPACT OF THE TIKTOK APP ON THE MENTAL HEALTH OF YOUNG USERS - Michał Ziemba; Anna Ziemba; Katarzyna Giedzicz; Rafał Kulgawczuk; Klaudia Zackiewicz; Agata Wińska; Oliwia Sędziak; Hanna Pietruszewska; Agata Ogórek; Irmina Czerepak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: In the 21st century, media significantly influences mental health. The TikTok app allows easy creation of videos and its algorithm adapts content to users interests. Aim: The following paper aims to analyse the impact of TikTok on the mental health of young users in the context of mood, eating and addiction disorders. Materials and Methods: Due to the dominance of users aged 16-24 on the TikTok platform, the research focused on the impact of the app on adolescent and young adult mental health. A review of papers available in bibliographic databases such as PubMed, Google Scholar and Web of Science was conducted, using the keywords: "TikTok", "mental disorders", "mental health", "eating disorders", "social media". Description of knowledge: Using TikTok can have both positive and negative effects. Positive aspects include an increased sense of social connection, reduction of stress and anxiety, and promotion of mental health issues by professionals. However, the app also carries risks, such as addiction, FOMO, misinformation, cyberbullying, impact on sleep quality and exposure to harmful content, and most importantly, exacerbates symptoms of mood and eating disorders. In order to minimise the negative effects of TikTok use, education about the potential risks is necessary. Conclusion: TikTok has the potential to have a positive impact on mental health as long as users use it consciously and in moderation, and the platform, educators and parents take steps to minimise the negative effects of children and young people using the app.